2022
DOI: 10.1111/scd.12732
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dental caries experience of Thai preschool children with cerebral palsy

Abstract: Aim To investigate the factors association with dental caries experience in the primary dentition of Thai preschool children with cerebral palsy. Methods and results A cross‐sectional study was conducted among sixty Thai preschool children with cerebral palsy, aged 3–6 years old. Caries experience was determined by identifying decayednon‐cavitated and cavitated lesion, missing, and filled surfaces of deciduous teeth(dmfs). Sociodemographic data, CP motor types, dietary habits, oral health behaviors and dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…When compared with previous research, our findings mirror those of Akhter et al [16], suggesting that children with severe motor functional impairments are at a higher risk of dental caries, likely due to challenges in maintaining proper oral hygiene. This notion is further supported by the observations made by Pansrimangkorn et al [17], where a substantial majority of preschoolers with CP were found to have dental caries, particularly those with spasticity.…”
Section: Discussionsupporting
confidence: 62%
“…When compared with previous research, our findings mirror those of Akhter et al [16], suggesting that children with severe motor functional impairments are at a higher risk of dental caries, likely due to challenges in maintaining proper oral hygiene. This notion is further supported by the observations made by Pansrimangkorn et al [17], where a substantial majority of preschoolers with CP were found to have dental caries, particularly those with spasticity.…”
Section: Discussionsupporting
confidence: 62%
“…Of these, ten studies were from African countries including Nigeria [ 21 – 24 ], Egypt [ 25 , 26 ], Cameroon [ 27 ], South Africa [ 28 ], Uganda [ 29 ], and Sudan [ 30 ]. Other studies were from Asian countries including Bangladesh [ 31 ], Saudi Arabia [ 32 – 34 ], India [ 35 37 ], Thailand [ 38 ], China [ 39 ], United Arab Emirates [ 40 ], Sri Lanka [ 41 ], Turkey [ 42 ], Iran [ 43 ], Pakistan [ 44 ], and Jordan [ 45 ]. Studies from 2008 to 2022 were included.…”
Section: Resultsmentioning
confidence: 99%